Height difference between the vestibular and palatal walls and palatal width: a cone beam computed tomography approach - P. López-Jarana; C. M. Díaz-Castro; A. Falcão; C. Falcão; J. V. Ríos-Santos; A. Fernández-Palacín; M. Herrero-Climent (BMC, 2021)
Abstract Background The objective of this study was to measure two parameters involved in tri-dimensional implant planning: the position of the buccal and palatal bone wall and the palatal thickness. Methods Cone beam computed tomography (CBCT) images (Planmeca ProMax 3D) of 403 teeth (208 upper teeth and 195 lower teeth) were obtained from 49 patients referred to the Dental School of Seville from January to December 2014. The height difference between the palatal and buccal walls was measured on the most coronal point of both walls. The thickness of the palatal wall was measured 2 mm from the most coronal point of the palatal wall. Results The mean values in the maxilla were 1.7 ± 0.9 mm for central and lateral incisors, 2.2 ± 1.7 mm for canines, 1.6 ± 0.9 mm for premolars and 1.9 ± 1.5 mm for molars. In the lower jaw, the mean values were 1.3 ± 0.8 mm for incisors, 1.7 ± 1.2 mm for canines, 2.3 ± 1.3 mm for premolars, and 2.6 ± 1.7 mm for molars. In the upper jaw, more than 55% of maxillary teeth (excluding second premolars and molars) presented mean height differences greater than 1 mm. In the mandible, more than 60% of incisors showed a buccal bone thickness of 1 mm from the apical to lingual aspect. All teeth except the second premolar presented a buccal wall located more than 1 mm more apically than the lingual bone wall. Conclusions The buccal bone wall is located more apically (greater than 1 mm) than the palatal or lingual table in most of the cases assessed. The thickness of the palatal or lingual table is also less than 2 mm in the maxilla and mandible, except in the upper canines and premolars and the lower molars.